Lessons from the Protestant Reformation for Today’s Islamic World - Hussein Solomon; Rene de Klerk (International Journal of Islamic Khazanah, 2023)
The Islamic world today faces multiple challenges, including political stagnation, religious authoritarianism, and societal inertia. Drawing on a historical-comparative approach, this article explores the Protestant Reformation as a case study to examine how religious renewal can emerge from within a faith tradition. The study employs a historical-analytical method, drawing parallels between key developments in the Reformation and current conditions in the Muslim world. By analyzing historical parallels, the authors argue that Islamic societies can benefit from lessons learned during the Reformation, particularly regarding the decentralization of religious authority, promotion of literacy, and critical engagement with sacred texts. The study finds that while the contexts differ, the need for internal reform and revival is shared. The article concludes that meaningful Islamic reform must originate from within Muslim societies and cannot be imposed externally. This analysis contributes to contemporary Islamic thought by encouraging critical reflection on religious tradition in light of historical experience, thus fostering a deeper understanding of reform in the modern Islamic context.